Impact of short term oral steroid use for intravenous contrast media hypersensitivity prophylaxis in diabetic patients undergoing nonemergent coronary angiography or interventions. Issue 7 (26th November 2019) - Amr, Bashar S.; Lippmann, Matthew; Tobbia, Patrick; Isom, Nicholas; Dalia, Tarun; Buechler, Tyler; Pierpoline, Michael; Patel, Nilay; Hockstad, Eric; Wiley, Mark; Tadros, Peter; Mehta, Ashwani; et al.
Abstract: Objectives: Oral steroids are routinely administered in the United States for prophylaxis of iodinated contrast media hypersensitivity (ICMH). We studied the impact of short‐term steroid use in diabetic patients with ICMH undergoing nonemergent coronary angiography. Methods: We retrospectively analyzed records of diabetic patients with and without ICMH who underwent nonemergent coronary angiography at our center. Primary study endpoint was 30‐day major adverse cardiac events (MACE) and secondary endpoints were pre‐ and postprocedure fasting blood glucose (FBG), highest in hospital blood glucose, pre‐ and postprocedure systolic blood pressure (SBP), and use of intravenous insulin and antihypertensive medications. Results: A total of 88 diabetics with ICMH (study group) and 76 diabetics without ICMH (control group) undergoing angiography were enrolled. Demographics and hemoglobin A1c values were similar in both groups. Preprocedural FBG was significantly higher in the study group. The study group had significantly higher post angiography FBG (239.93 + 96.88 mg/dl vs. 156.6 + 59.88 mg/dl) and greater use of intravenous (IV) insulin (67.27% vs. 32.43%). Further, those who received steroids had significantly higher systolic SBP postprocedure (146.16 + 25.35 mmHg vs. 130.8 + 21.59 mmHg), a higher incidence of severe hypertension and use of IV antihypertensive medications (80.95% vs. 19.05%) periprocedurally. There were no differences in 30‐day MACE between groups. Conclusion: Short‐term steroid use for ICMH results in a significant increase in surrogate markers for adverse clinical events after coronary procedures. Study findings highlight the need for better periprocedural management of these patients and to limit steroid prophylaxis to those with only true ICMH.